Cartography and Art - SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book is the fruition of work from contributors to the Art and Cartography: Cartography and Art symposium held in Vienna in February 2008. This meeting brought together cartographers who were interested in the design and aesthetics elements of cartography and artists who use maps as the basis for their art or who incorporate place and space in their expressions. The outcome of bringing together these like minds culminated in a wonderful event, spanning three evenings and two days in the Austrian capital. Papers, exhi- tions and installations provided a forum for appreciating the endeavors of artists and cartographers and their representations of geography. As well as indulging in an expansive and expressive occasion attendees were able to re? ect on their own work and discuss similar elements in each other$1 (Bs work. It also allowed cartographers and artists to discuss the potential for collaboration in future research and development. To recognise the signi? cance of this event, paper authors were invited to further develop their work and contribute chapters to this book. We believe that this book marks both a signi? cant occasion in Vienna and a starting point for future collabo- tive efforts between artists and cartographers. The editors would like to acknowledge the work of Manuela Schmidt and Felix Ortag, who undertook the task of the design and layout of the chapters.s
Theory -- Art and Cartographic Communication -- Rejecting Illusionism: Transforming Space into Maps and into Art -- From a Cartographic Glance to Synchronistic Experiences -- Marriage and Divorce: Is the Evolution of Landscape Paintings Ending in the Fields of Topographic Cartography and Graphic Design? -- Maps and Mapping in the Eyes of Artists and Cartographers#x2013;Experiences from the International Symposium on Cartography and Art -- Aesthetics and Cartographic Design -- Are we Living in a Cartographic Illiterate Society? -- Aesthetics of the CORINE Land Cover Maps -- Making Legends By Means of Painters#x2019; Palettes -- What Can We Learn from the Masters? Color Schemas on Paintings as the Source for Color Ranges Applicable in Cartography -- The Role of Augmented Elements to Support Aesthetic and Entertaining Aspects of Interactive Maps on the Web and Mobile Phones -- Variables of Aesthetics in Maps -- Art and the History of Cartography -- World-Views: Art and Canonical Images in the Geographical and Life Sciences -- Map Style -- The World Image in Maps #x2013; From the Old Ages to Mercator -- Integrated Media -- Mapping Literature: Towards a Geography of Fiction -- Challenging the Digital Cartographic Continuity System: Lessons from Cinema -- On Written Language in Works of Art and Cartography -- Imagining Europe -- Non-Graphics -- Dots, Lines, Areas and Words: Mapping Literature and Narration (With some Remarks on Kate Chopin#x2019;s #x201C;The Awakening#x201D;) -- Robert Smithson#x2019;s Pursuit: Mapping some Traces of Remnants -- Towards a Literary Geography of the Interwar Australian Novel -- Mapping Informal Geographies -- Mapping the Sacred Landscape of Lahaul #x2013; The Karzha Khandroling Mandala -- Art and Media Design -- Sculpting Place Through Ceramic Maps -- The Map of Fashion -- Maps of What Might Be: A Dozen Works on Ideas and Possibilities -- On Sustenance: Operating Landscapes, Land Spaces and Land#x2019;s Paces -- Social Tapestries -- Community Karlsplatz, ViennaVideo Screen Projection -- 4816 #x2013; Urban Expeditions in Vienna Along the GPS Matrix -- Installation Art -- Dream but Conflict -- Pressure Today -- Early-Modern Portuguese Maps: Metaphors of Space and Spaces of Metaphor -- This Is Not a Map.
Keywords: Geography; Geographical information systems; Graphic design; Geography; Geographical Information Systems/Cartography.; Graphic Design; Electronic books